Protective Role of Pomegranate Peel Extract on Testis in Adult Male Rabbits Treated with Carbon Tetrachloride: Wassan M. Hussen and Jawad K.Arrack - Hussen, Wassan M. (The Iraqi Journal of Veterinary Medicine, 2014)
The aim of the present study is to prepare ethanol extract of Pomegranate peel and the effects of this extract on testicular weight to body weight ratio, Serum cholesterol, testosterone concentration and histopathological changes of testes in rabbits treated with carbon tetrachloride (CCl4). Twenty four adult male rabbits were used. They were divided randomly into four equal groups. Animals were treated for 56 days as following: Rabbits of the 1st group were received 1 ml distal water orally once a day and olive oil 0.5 ml /kg B.W. I.P twice a week as control group. The second group were treated I.P with 500mg / kg B.W. of CCl4 mixing with equal volume of olive oil (0.5 ml/kg B.W.) twice a week (group T1). The third group was received pomegranate peel extract orally (100 mg/kg B.W) once a day and olive oil 0.5 ml /kg B.W. I.P twice a week (group T2). The fourth group were received pomegranate peel extract (100 mg/kg B.W) once a day oral I.P with 500 mg / kg B.W. of CCl4 mixing with equal volume of olive oil (o.5 ml/kg B.W.) twice a week (group T3). Blood samples were collected at (0, 14, 28, 42 and 56) days for measuring testosterone concentration, Serum cholesterol after treatments. Animals weighed and scarified and testis were removed and weighed, Samples of testis were taken for histopathological study. The results of the present study showed that treatment with pomegranate peel extract causes a significant (P>0.05) increase in testicular weight to body weight ratio. Also a significant (P>0.05) decreased of serum cholesterol and a significantly (P>0.05) elevation of testosterone concentration were observed. Histopathological examination of the testis was revealed that the extract of Pomegranate peel protect the testis against lesions caused by CCl4. In conclusion, Pomegranate peel extract could protect the tissue of testicles from CCl4 perhaps, by its anti-oxidative effect of pomegranate peel extract, hence eliminating the deleterious effects or toxic effect of CCl4.